2020
DOI: 10.1021/acs.jproteome.0c00271
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Sensitive Analysis for Dried Blood Spot Proteins by Sodium Carbonate Precipitation for Clinical Proteomics

Abstract: Dried blood spots (DBS) are widely used for screening biomolecular profiles, including enzymatic activities. However, detection of minor proteins in DBS by liquid chromatography–mass spectrometry (LC-MS/MS) without pre-enrichment remains challenging because of the coexistence of large quantities of hydrophilic proteins. In this study, we address this problem by developing a simple method using sodium carbonate precipitation (SCP). SCP enriches hydrophobic proteins from DBS, allowing substantial removal of solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
(53 reference statements)
1
19
0
Order By: Relevance
“…There was an average of 900, 757, 644, and 621 protein identifications made for the WP, PF, WP Disc, and PF Disc sample preparation methods (SPMs), respectively, which offers many possibilities for biomarker discovery and analysis. When compared to WP, the PF, PF Disc, and WP Disc SPMs still performed relatively well considering dried plasma and blood spots generally have lower recoveries and identifications of proteins relative to regular plasma samples ( Chambers et al, 2013 ; Nakajima et al, 2020 ). In order to estimate protein recoveries for SPMs, we calculated the fold change of the SPMs relative to WP.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There was an average of 900, 757, 644, and 621 protein identifications made for the WP, PF, WP Disc, and PF Disc sample preparation methods (SPMs), respectively, which offers many possibilities for biomarker discovery and analysis. When compared to WP, the PF, PF Disc, and WP Disc SPMs still performed relatively well considering dried plasma and blood spots generally have lower recoveries and identifications of proteins relative to regular plasma samples ( Chambers et al, 2013 ; Nakajima et al, 2020 ). In order to estimate protein recoveries for SPMs, we calculated the fold change of the SPMs relative to WP.…”
Section: Discussionmentioning
confidence: 96%
“…Over 90% of proteins detected within the current dataset had negative GRAVY values suggesting that both proteomics sample preparation methods (i.e., Bligh-Dyer extraction or dissolution in AB buffer) select a similar range of mostly hydrophilic proteins regardless of the SPM used. Hydrophobic, native proteins tend to occupy cellular membranes and are not recovered well without specialized sample extraction protocols such as the use of a detergent ( Ludwig et al, 2018 ; Nakajima et al, 2020 ). It was expected that the PF DPS may affect the abundances of hydrophobic proteins considering it is a polymer primarily composed of paraffin waxes and polyolefins which create a non-polar support material, but there were few hydrophobic proteins identified within the dataset ( Miller, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the DIA-based approach can be considered an improvement in in-depth DBS proteomics over the DDAbased approach, the depth of proteome coverage is still far from satisfactory. We also attempted to improve DBS proteome analysis with an improved DIA method, that is overlapping windows DIA [48]; we were able to obtain slightly more DBS proteome data using this method, as shown in Table 2 [49]. The depth of DBS proteome analysis was further improved by first fractionating the mass range to five fractions using gas phase fractionation and then applying overlapping window DIA measurements (Table 3).…”
Section: Proteome Analysis Of Dbss: Nontarget Approachesmentioning
confidence: 99%
“…When nontarget proteome analysis is intended for use with NBS, it is expected to expand the range of DBS proteins detected by LC-MS/MS analysis with prefractionation to levels equivalent to those achieved with high-throughput analysis in terms of cost and labour. Although few studies have tackled this issue in DBS proteome analysis [49,50], we recently demonstrated that precipitation with sodium carbonate might be useful for this purpose (Table 3) [49].…”
Section: Proteome Analysis Of Dbss: Nontarget Approachesmentioning
confidence: 99%
See 1 more Smart Citation